Paleocontraintes et Contexte Tectonique de Mise en Place du Volcanisme Alcalin Neogene et Quaternaire du Moyen Atlas (Maroc) - Saïd Hinaje; Mohamed El Fartati; Driss Yaagoub; Samir Amrani; Youssef Gharmane; Bouhsine El Fellah Idrissi (European Scientific Journal, ESJ, 2019)
During the Neogene and Quaternary periods, the Middle Atlas was characterized by a volcanic activity in relation to complex magmatic-tectonic phenomena. Volcanoes belong to the strombolian and maar types. This volcanic activity began in the Miocene by alkaline flows, sills, dykes and volcanic caps. The pyroclastic rocks emitted by volcanoes correspond to alkali basalts, basanites and nephelinites. Because of the morphologicalrelationships existing between the recent hydrographic system, the last volcanic lavas and the sub-meridian grabens; the Middle Atlas basalts have been assigned, without field structural arguments, to the last Quaternary tectonic phase. The purpose of this paper is to expose the results of the study of the distribution of volcanoes in relation to the tectonic alignments. The volcanic edifices are aligned along the N130, N70, N40 and N170 directions, with a predominance of the N130 trend. For example, the Timahdite-Azrou volcanic zone can be interpreted as a NW-SE graben filled with Late Miocene fluvial and lacustrine deposits. Another example of volcanic activity related to transtensional openings at the junction zones between antithetic faults (tectonic nodes) can be found around the Zelghi, Aguelmam Sidi Ali, Oum Larays and TafraouteAit Bouziane volcanoes. The most recent volcanoes are associated with middle – late Quaternary normal sub-meridian faults like the volcanoes of Azghar-Boutferoun located in the Anoceur and Amekla plateau (causses).Au cours de la période néogène et quaternaire, le Moyen Atlas a connu une activité volcanique en relation avec des phénomènes magmatiques et tectoniques complexes. Plusieurs dizaines d’édifices volcaniques appartiennent aux types stromboliens et maars. Ce volcanisme a commencé au Miocène par des coulées, des sills, des dykes et des culots de nature alcaline. Les produits pyroclastiques émis correspondent à des basaltes alcalins, à des basanites et à des néphélinites. En raison des relations morphologiques entre le réseau hydrographique actuel, les dernières laves volcaniques et les grabens subméridiens; les basaltes du Moyen Atlas ont été attribués, sans argument structural, à la dernière phase tectonique du Quaternaire. Le but de cette note est d’exposer les résultats de l’étude de la répartition des volcans suivant les alignements tectoniques en relation avec les phases de déformation. Les édifices volcaniquessont alignésselon les directions N130, N70, N40 et N170, avec une prédominance de la direction N130. Un exemple de ce dernier alignement est la zone volcanique Timahdite-Azrou que nous interprétons comme un graben orienté NW-SE, à remplissage fluvio-lacustre au Miocène supérieur. Un autre exemple d’activité volcanique est celle liée à des ouvertures en transtension dans les zones de jonction entre des failles antithétiques(nœudstectoniques); comme les volcans de Zelghi, d’Aguelmam Sidi Ali, de Oum Larays et de Tafraoute-Aït Bouziane. Les volcans les plus récents sont associés aux failles normales subméridiennes d’âge quaternaire moyen-récent, comme ceux d’Azghar-Boutferoun situés dans les causses d’Anouceur et d’Amekla.